Application of Complementary Split Ring Resonator for Hyperthermia - Rahmawati Yusri; Muldarisnur Muldarisnur (Jurnal Ilmu Fisika, 2021)
One of the most promising research for cancer therapy with less side effects is hyperthermia treatment using metamaterial. This treatment may stand independently or adjunct to other cancer treatments such as chemotherapy, radiotherapy, and others. Metamaterial may control the heating process needed and also the depth of metamaterial itself from the skin surface. In this simulation, complementary split-ring resonator (cSRR) metamaterial with gaps from 0.5 to 3.5 mm can be used for the hyperthermia treatment. In the simulation of the cSRR metamaterial as hyperthermia therapy for cancer cells, the heat generated from each cSRR model was not significantly different. All cSRR models can reach hyperthermal temperatures under 5 minutes. The highest temperature achievement after 60 minutes can be seen in the use of single gap cSRR (58.9 ℃), dual gaps cSRR (58.1 oC), triple gaps cSRR (57.5 ℃), and quad gaps cSRR (57.2 ℃). The cSRR metamaterial structure can be used for hyperthermia therapy by adjusting the treatment duration treatment on cancer cells.